Clonal evolution of esophageal squamous cell carcinoma from normal mucosa to primary tumor and metastases. (1st October 2019) - Yuan, Wenqing; Liu, Zhen; Wang, Yu; Liu, Mengfei; Pan, Yaqi; Lei, Wanjun; Yang, Haijun; Xu, Ruiping; Zhang, Lixin; Cai, Hong; Li, Jun; Ke, Yang
Abstract: The clonal evolution which drives esophageal squamous cell carcinoma (ESCC) from initiation in normal cell to primary carcinoma and metastases is poorly understood. In this study, multi-region whole-exome sequencing (WES) (284X) and whole-genome single nucleotide polymorphism genotyping were performed on a total of 109 samples of ESCC from 10 patients. This included 42 apparently normal samples of esophageal mucosa at increasing distances from the upper or lower boundaries of the primary tumor to the surgical margins of resection, 43 spatially separated tissue samples within primary tumor and 24 regional lymph node metastases. Phylogenetic analysis was performed to reconstruct ancestor–descendant relationships of clones and the clonal composition of multi-region samples. Mutations of cancer-related genes were validated by deep targeted sequencing (1, 168X). Both inter- and intra-tumoral genetic heterogeneity were obvious across multi-region samples among ESCC patients. Clones varying in number from one to seven were discovered within each regional tumor or metastatic sample. Phylogenetic analysis demonstrated complex clonal evolution patterns. Regional lymph node metastases had characteristics of early initiation and polyclonal spreading, and could be derived from carcinoma in situ (CIS) directly. TP53 was the only gene harboring non-silent mutations identified across all multi-region tumor samples of all ten patients. Mutations of TP53 were also found in histologically normal mucosa in sites away from primary tumor.